(3TQM CQLhRI GHf CHj GdQLGds - (3CMeO Hf MSjf Hf Ydj Hf (B((3bfaP(B) (3GdbSfWjfis; (3Ydj Hf CHj GdQLGd GdTjHGfj, CHh GdMSf GdeZQHj GdbjQhGfj,J (B432 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdNdb HbOQJg , hejRge HMceJg hHYO aEfg deG cGf SjO GdhRQGA SjOfG CHj jMji GHf SjfG GdeQMhe CHj eLGgO ZGRi CLd ef NOe HCZdi GdYdhe GdYbdjI bOQkG s
(3BNQgG (B:s
(3hjOd CjVkG Ydi GdUhGYb hGdHQO , dCf GdcGJH eeJRL hGddg CYde hgGgfG GfJgi GdZQV ai gPG GdTQM GdeHGQc , hLGA HMeO Gddg TGedkG cGajI def JOHQgG hCMce CUhdgG s
(3HgG fXGe GdJYbjHIs
(3HgG LOGhds
(3fSNI KGdKIs
(3JJab ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGX s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdadcs